The Effects of a 48-Hour Fasting Period on Metabolic Markers During Exercise and Recovery in Male Combat Sports Athletes (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Fasting strategies have gained increasing attention in sports science due to their potential effects on metabolic responses and athletic performance. However, limited research has examined the metabolic and performance-related consequences of a 48-hour fasting period followed by a 24-hour recovery phase in combat sports athletes. This study aims to investigate the effects of 48-hour fasting on metabolic markers, performance, and recovery in male combat sports athletes, emphasising the reversibility of fasting-induced metabolic changes after a 24-hour refeeding period.Methods: A total of eight male combat sport athletes ([Mean ± standard deviation] Age: 25.1 ± 4.0 years, Height: 181 ± 6.7 cm, Body Weight: 83.3 ± 12.7 kg) participated in this interventional pre- and post- study. The research design included three assessment points: before fasting (baseline), after 48 hours of fasting, and after a 24-hour recovery period. The measured variables included: the resting metabolic rate (RMR), V̇O2max test data, lactate, glucose and ketone, free fat mass (FFM), body weight.Results: Fasting significantly decreased FFM (–1.4 ± 10.8 kg, p < 0.008) and body weight (–2.1 ± 12 kg, p < 0.001). V̇O2max test load decreased significantly (13 Watts, p < 0.001) after fasting but returned to baseline after 24-hour recovery. Ketone levels increased significantly (1.04 ± 0.51 mmol/L, p < 0.001). Peak glucose levels also decreased significantly (0.8 ± 0.70 mmol/L, p < 0.028), along with glucose levels at the 2nd (0.7 ± 0.51 mmol/L, p < 0.001) and 15th (0.6 ± 0.70 mmol/L, p < 0.005) minutes of recovery. Lactate concentrations decreased significantly during peak performance (10.3 ± 4.03 mmol/L, p < 0.049) and 30-minute recovery (5.5 ± 1.60 mmol/L, p < 0.005).Conclusion: This study demonstrates that a 48-hour fasting period significantly alters metabolic markers and temporarily impairs V̇O2max performance. However, after a 24-hour recovery period, performance measures returned to baseline, suggesting that 48-hour fasting does not have long-lasting adverse effects on performance in combat sports athletes. These findings highlight the metabolic adaptability of trained athletes and the potential implications of fasting as a weight management strategy. Further research is required to explore the long-term physiological effects and potential applications in combat sports training and competition.Support/Funding Source: This work was supported by the Research Council of Lithuania (Grant Number S-PAD-22-9).